Synthesis of an arrayed sgRNA library targeting the human genome - Schmidt, Tobias (Sci Rep, 2015)
Clustered regularly interspaced short palindromic repeats (CRISPR) in conjunction with CRISPR-associated proteins (Cas) can be employed to introduce double stand breaks into mammalian genomes at user-defined loci. The endonuclease activity of the Cas complex can be targeted to a specific genomic region using a single guide RNA (sgRNA). We developed a ligation-independent cloning (LIC) assembly method for efficient and bias-free generation of large sgRNA libraries. Using this system, we performed an iterative shotgun cloning approach to generate an arrayed sgRNA library that targets one critical exon of almost every protein-coding human gene. An orthogonal mixing and deconvolution approach was used to obtain 19,506 unique sequence-validated sgRNAs (91.4% coverage). As tested in HEK 293T cells, constructs of this library have a median genome editing activity of 54.6% and employing sgRNAs of this library to generate knockout cells was successful for 19 out of 19 genes tested.